On the identity of the type species of Sphenomorphus (Squamata: Scincidae): Lygosoma melanopogon Duméril and Bibron 1839, with a note on a new scalation character of the pes in Sphenomorphus - Shea, Glenn M. (Zootaxa, 2012)
The type series of Lygosoma melanopogon Duméril and Bibron 1839, the type species of the scincid lizard genusSphenomorphus Fitzinger 1843, consists of four specimens representing three species, all of which have available juniorsynonyms. A lectotype is designated, and Lygosoma melanopogon becomes a senior synonym of Lygosoma florenseWeber 1891 (= Sphenomorphus florensis) and that species is redefined based on specimens from throughout itsdistribution for the first time. Based on a lack of consistent differences in morphology and coloration, previously namedsubspecies of Sphenomorphus florensis are placed in synonymy, leaving a single wide-ranging species S. melanopogon.Lygosoma Kühnei Roux 1910 is also placed in the synonymy of S. melanopogon, and the nomenclatural status of the nameScincus naevius Duméril and Bibron 1839 resolved. Lygosoma Meyeri Doria 1874 is raised from synonymy to becomethe name for the New Guinean Sphenomorphus species to which the name S. melanopogon has sometimes previously beenapplied, and Hinulia papuensis Macleay 1877 synonymised with it. Sphenomorphus melanopogon is identified as amember of a group of Sphenomorphus species which show an extension of the imbricate dorsal scalation onto the solar surface of the pes.